Mitofusin-2 Restrains Hepatic Stellate Cells' Proliferation via PI3K/Akt Signaling Pathway and Inhibits Liver Fibrosis in Rats. (17th January 2022) - Chen, Zhiping; Lin, Zeyu; Yu, Jiandong; Zhong, Haifeng; Zhuo, Xianhua; Jia, Changku; Wan, Yunle
Abstract : The mitochondrial GTPase mitofusin-2 ( MFN 2) gene can suppress the cell cycle and regulate cell proliferation in a number of cell types. However, its function in hepatic fibrosis remains largely unexplored. We attempted to understand the mechanism of MFN 2 in hepatic stellate cell (HSC) proliferation and the development of hepatic fibrosis. Rat HSC-T6 HSC were cultured and transfected by adenovirus- (Ad-) Mfn 2 or its negative control (NC) vector (Ad-green fluorescent protein (GFP)); a rat liver cirrhosis model was established via subcutaneous injection with carbon tetrachloride (CCl4 ). Seventy-two rats were randomly divided into four groups: CCl4, Mfn 2, GFP, and NC. Ad- Mfn 2 or Ad-GFP was transfected into the circulation via intravenous injection at day 1, 14, 28, 42, or 56 after the first injection of CCl4 in the Mfn 2/GFP groups. Biomarkers related to HSC proliferation and the development of hepatic fibrosis were detected using western blotting, hematoxylin-eosin and Masson staining, and immunohistochemistry. In vitro, Mfn 2 interfered specifically with platelet-derived growth factor- (PDGF-) induced signaling pathway (phosphatidylinositol 3-kinase- (PI3K-) AKT), inhibiting HSC-T6 cell activation and proliferation. During the process of hepatic fibrosis in vivo, extracellular collagen deposition and the expression of fibrosis-related proteins increased progressively, while Mfn 2 expression decreased gradually. Upregulating Mfn 2 expression at the early stage of fibrosis impeded the process, triggered the downregulation of type I collagen, and antagonized the formation of factors associated with liver fibrosis. Mfn 2 suppresses HSC proliferation and activation and exhibits antifibrotic potential in early-stage hepatic fibrosis. Therefore, it may represent a significant therapeutic target for eradicating hepatic fibrosis.